2020
DOI: 10.26641/2307-0404.2020.1.200407
|View full text |Cite
|
Sign up to set email alerts
|

Features of depression development in myasthenia gravis.

Abstract: Features of depression development in myasthenia gravis. Kalbus O.I., Makarov S.O., Shastun N.P., Somilo O.V., Bukreyeva Yu.V. The relative risk of developing depression in myasthenia gravis is 2.14 times higher than in the general population. The features of depression in myasthenia patients remain poorly understood and need to be clarified. The purpose of this work was to study the features of the development of depression in patients with myasthenia gravis. From 2014 to 2017, 182 patients with myasthenia gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the study of O.I. Kalbus et al [49] the hypothesis regarding the effect of disease duration on the development of depression was not confirmed, and there were no statistically significant correlations between the Beck score and disease duration.…”
Section: Discussionmentioning
confidence: 88%
“…In the study of O.I. Kalbus et al [49] the hypothesis regarding the effect of disease duration on the development of depression was not confirmed, and there were no statistically significant correlations between the Beck score and disease duration.…”
Section: Discussionmentioning
confidence: 88%
“…According to studies about the prevalence of anxiety and depression in MG, the epidemiology of depression in MG varies from 6% to 76% (Kalbus et al., 2020 ; Sivadasan et al., 2019 ) and anxiety varies from 3% to 71% (Sivadasan et al., 2019 ; Ybarra et al., 2011 ). So, evidence showed that MG individuals are inclined to show high rate of depression and anxiety, and studies confirmed that anxiety and depression affect the mental health of MG people.…”
Section: Introductionmentioning
confidence: 99%